Linux Foundation Certified System Administrator (LFCS) : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2017)
Linux Foundation Certified System Administrator (LFCS) Complete Video Course has 14 hours of comprehensive video training‚Äîwhich includes whiteboard concept teaching, live CLI work, screencast teaching, hands-on labs, and practice exam walkthroughs‚Äîso you have everything you need to study for and pass the LFCS exam. This course will give you practical and reliable training, so you get all the information you need to pass the LFCS exam, as well as the real-world experience you need to fully understand concepts and practice your skills.